Gene expression of transcripts encoding putative secreted proteins from an oil palm fungal pathogen Ganoderma boninense - Jee, Mui Sie; Ho, Chai Ling; Yusof, Mohd Termizi; Lau, Sharon Yu Ling; Midot, Frazer; Lo, Mei Lieng; Chin, Mei Yee; Melling, Lulie (Academic Press, 2025)
Ganoderma boninense is a white rot fungus which causes basal stem rot (BSR) disease in oil palm and economic loss to the oil palm industry in Southeast Asia. The existing solutions for the disease are ineffective and the genetic determinants responsible for the disease occurrence are understudied. This study reported the characterisation of four transcript sequences encoding metalloproteinase (U14090), aspartic protease (U42611), lipase (U56931), and polysaccharide deacetylase (U128397) from G. boninense. The candidate transcripts were cloned and confirmed by sequencing. The gene expression of U56931 was up-regulated in mycelial cultures at 21- and 28-days after inoculation (dai) whereas the expression of U42611 was down-regulated in mycelial cultures at 28-dai, in comparison to that at 7-dai. Salicylic acid which is involved in plant biotic stress response was shown to be able to down-regulate the gene expression of U56931. The gene expression of U14090 was up-regulated in G. boninense in contact with oil palm roots for 24- and 48-h post inoculation (hpi) compared to that in the uninoculated control. The findings of this study may facilitate the design of future functional studies and help to prioritise candidate fungal genes for gene editing.